"James Rorke, Hilda Forward Pike, ?, Harry Archibald and Mary Rorke Archibald, Fulford's Hotel, Placentia, Nfld" - Rorke Family (1925)
James Rorke, Hilda Samways (Forward) Pike, Kathleen (Forward) Rorke, Harry Archibald and Mary (Rorke) Archibald and two unidentified men, standing outside on the front bridge of Fulford's Hotel in Placentia, Newfoundland. James Rorke (1890-1947), son of James Addy Rorke and Mary (Wilcox) Rorke, was born 13 April 1890. He married Kathleen Forward (1894-1979), daughter of Ernest Edward Forward and Tryphena (Butt) Forward, on 23 May 1917, and had three children: Patricia (Rorke) Yorke, James Ernest Rorke and Yvonne (Rorke) Pratt. Like his father, he worked with the family company, John Rorke and Sons, Limited. He died on 14 May 1947 in Carbonear. His sister was Mary (Rorke) Archibald (1888-1952), born in 1888 at Carbonear. She married Henry ''Harry'' Archibald of Harbour Grace in 1909. She died in 1952. Hilda Samways (Forward) Pike (1889-1982), sister of Kathleen (Forward) Rorke and the second of three daughters of Ernest Edward Forward and Tryphena (Butt) Forward, was born on 5 June 1889. Her grandfather was Captain Mark William Forward. She married her sister Ernestine's former husband, Arthur S. Pike, on 5 June 1951, over a year after her sister died. Hilda died in 1982. The Rorke Family Photograph Collection contains 301 black and white and 28 colour photographs of the Rorke Family of Carbonear, Newfoundland, as well as the Forward and Bemister families from that area who are linked to it by marriage. Although spanning from the 1840s-1970s, most photos are from 1900-45, showing family events, homes and Newfoundland and Labrador locations. There is also an album of photos taken while James Rorke attended the Leys School in Cambridge, England.